Snow Fortifications as Protection against Shaped Charge Antitank Projectiles - Farrell, Dennis (1980)
This report chronicles an investigation of the effectiveness of snow fortifications. The test was planned to observe and measure how packed snow absorbs the energy of high explosive antitank (HEAT) ammunition. In the test plan we considered both the possibility of non-detonation due to insufficient resistance in snow and the rate of deterioration of a snow embankment with repeated impacts. The 90-mm M67 recoilless rifle was used because it has a relatively low velocity and its charge was more likely to not detonate than that of a high velocity weapon. The charge weight and configuration were similar to other ammunition of this caliber. We found that: (1) 29 of 30 live rounds detonated on impact; (2) damage to inert rounds which were retrieved from the embankment ranged from slight to negligible; (3) maximum penetration of the shaped charge was less than 3.5 m; maximum penetration of the inert rounds was less than 3.0 m; and (4) a packed snow embankment does not deteriorate rapidly under sustained fire. These findings indicate that snow can be used to good advantage for building expedient fortifications, particulary in situations where large volumes of snow have to be cleared from roads and airfields.